Ideology and Contradictions within the Framework of the “Great Alliance” during World War II: Array - Ștefan, Gheorghe (Acta Universitatis Danubius. Relationes Internationales, 2022)
One of the classical theses of Marxism presumes that any revolution, aside from the communist one, bears the seeds of a new revolution to follow. This thing can certainly be stated about wars as well. For instance, during World War II (1939-1945), the opinions of most specialists concorded with the idea that the “war had not yet ended when the next had already begun”, said the illustrious historian- A. Fontaine.